Research Report on Curse the Fiends, Their Children, Too: Cultural Heritage and Subversion of Fictional Tropes in Bloodborne - Zaidan, Sarah (Gamevironments, 2019)
Directed by Hidetaka Miyazaki, From Software s multi-award winning 2015 action role-playing game Bloodborne was lauded for its game design and intriguing setting. Miyazaki as a creator frequently makes use of subversion of expectations established through narrative tropes to criticize and imbue the player s interaction with the game with more complex meaning than first appears. Although set in an entirely fictional world, Bloodborne draws explicitly on Catholicism, Gothic horror tropes and European architecture. However, these are then used to explore a specifically Japanese set of themes, with extensive use of Shinto and Buddhist ideas throughout. The use of Western symbols of cultural heritage also functions to interrogate these symbols for a Western audience, with the game explicitly invoking and then subverting recognizable iconography, destabilizing something initially presented as classic. By applying sociological literary criticism to the world and characters of Bloodborne, we are in the process of engaging with social and literary themes guided by a review of literature pertaining to both Japanese history and the roots of the Western iconography that the game draws upon to create its aesthetic. We are focusing on the various forms Japanese cultural heritage takes in Bloodborne, both as it is presented through game and visual design, and how those elements, in addition to its Western cultural elements are used to engage and interrogate Japanese cultural heritage.